Data Registry on Experiences of Aging, Menopause, and Sexuality (DREAMS): A cohort profile. (January 2018) - Faubion, Stephanie S.; Kapoor, Ekta; Kling, Juliana M.; Kuhle, Carol L.; Sood, Richa; Rullo, Jordan E.; Thielen, Jacqueline M.; Shuster, Lynne T.; Rocca, Walter A.; Hilsaca, Karla S. Frohmader; Mara, Kristin C.; Schroeder, Darrell R.; et al.
Highlights: DREAMS contains data on more than 8000 women seen at Mayo Clinic in Rochester, Minnesota, since 2005. The registry includes pertinent patient information from various standard questionnaires. The DREAMS data can be used for passive longitudinal studies and randomized controlled trials. Linkage to other databases could provide additional information on participants. Abstract: The Women's Health Clinic (WHC) at Mayo Clinic in Rochester, Minnesota, has provided consultative care to women with menopausal and sexual health concerns since 2005. Clinical information on the 8688 women seen in the WHC through May 2017 who gave consent for the use of their medical records in research is contained in the Data Registry on Experiences of Aging, Menopause, and Sexuality (DREAMS). Initially, DREAMS was created to improve the clinical care of women, but it has become a valuable research tool. About 25% of the DREAMS women have been seen in the WHC 2 or more times, allowing for passive longitudinal follow-up. Additionally, about 25% of the DREAMS women live in the 27-county region included in the expanded Rochester Epidemiology Project medical records linkage system, providing additional information on those women. The cohort has been used to investigate associations between: caffeine intake and vasomotor symptom bother; recent abuse (physical, sexual, verbal, and emotional) and menopausal symptoms; specific menopausal symptoms and self-reported view of menopause; and obstructive sleep apnea risk and vasomotor symptom severity and the experience of vasomotor symptoms in women older than 60 years. A study nearing completion describes a clinical series of over 3500 women presenting for sexual health consultation by sexual function domain and by decade of life. Other studies under way are determining correlates with sexual health and dysfunction. Planned studies will investigate associations between the experience with menopause and the risk of disease.